Primacy of the Bishop of Rome in the Magisterium of the First Vatican Council and the Codes of Canon Law of the 20th century - Rozkrut, Tomasz (Prawo Kanoniczne, 2021)
The First Vatican Council (1869-1870) convened by Pope Pius IX by the “Aeterni Patris” bull of 29 June 1868, that was ceremoniously opened on June 8, 1869 by and in chairmanship of this Pope in the Saint Peter’s Basilica, in “Pastor aeternus”, i.e. in the first Dogmatic Constitution in the Church of Christ presented a doctrine on the primacy and infallibility of the Bishop of Rome. From the time perspective it is good to indicate that this Council did not give any statement on the collegiality of the episcopal church. This may make its magisterium to be seen as incomplete from the historical point of view. However, it must be remembered that, first of all, it was due to the fact that at this historical moment of time this subject did not require such attention as was required by other urgent issues defined during the Council. Announcing dogmas on the primacy and infallibility of the Bishop of Rome without a definite determination of collegiality of the bishops’ authority pushed minds towards researches of even greater intensity. They were intended to deepen the idea of the Church’s collegiality. Undoubtedly, this resulted from the fact that in the Magisterium of the First Vatican Council, that can be called the First Ecclesiology Council, the figure of the Bishop of Rome was presented in an isolated manner, separated from a broader ecclesiology context and collegiality of the episcopal church. Though, one can also find expression presenting the problem of collegiality of the episcopal church in the “Pastor Aeternus”. There is no doubt whatsoever that this what was said and written through the centuries about the person and office of the Bishop of Rome, in particular in regards to its primacy and infallibility, denotes a fundamental, it means basic role of every pope in the universal history of the Church and the entire mankind, in the broader sense. In such an outlined perspective, the doctrine of the First Vatican Council appears to be very important. Its consequences can be found in the Church’s successive codifications, whereas its development and supplementation can be found in the teaching of the Second Vatican Council